Identifikasi Pengaruh Income, Financial Knowledge, dan Lifestyle pada Personal Financial Management Generasi Echo Boomers - Hidayah, Zulfa Zakiatul; Syahwildan, Muhamad; Pratiwi, Rizka Estisia (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
Times are growing and so are the generations, there are so many changes in the current generation. In 2023, the term work-life balance became popular again, which has actually been around since 1986. To support this kind of lifestyle, it also requires optimal management of the aspects of life, especially the financial aspects. Discussing finances is very crucial, because many people change their life priorities because of this. This study will further analyze a person's financial management behavior and some aspects that influence it such as a person's income and their knowledge of finance. The purpose of this study is to determine the factors that influence financial management behavior which include Income, Financial Knowledge, and Lifestyle conducted on the Echo Boomers Generation or the millennial generation which will be specialized in the Bekasi area which has a female gender. The data source of this study uses primary data originating from original data by data collectors using a questionnaire as a data collection technique for 100 respondents. The sampling technique used Accidental sampling on millennials in the Bekasi area. The research method uses a quantitative approach with statistical methods. The study conducted by researchers is to measure the positive influence of several indicators on each variable in it by using statistical test tools with PLS.